MOTIVASI KARYAWAN DAN KEDISIPLINAN KERJADALAM PELAYANAN SEHINGGA MENGHASILKAN KEPUASAN KONSUMEN PADA PERUSAHAAN MINUMAN - rensiana ninut; Amirullah, Indriati; Prully c. Yahdus (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2021)
Drink company (beverage shop) is one of the shops in Makassar that has various kinds of drink syrup and drink powder, and there are several complementary ingredients in the cafe.The agent who owns the drink company's shop is Mr. Deril Tunggal. The main reason Mr. Deril Tunggal opened this shop is because he is affected by the weather conditions in Indonesia, which always tends to be in the summer, so many people need fresh drinks.The purpose of this research in this store is to find out and observe the workings associated with the employees and store leaders of the drink company and customer satisfaction. And also this research was conducted to find out how leaders guide their employees and customer satisfaction in receiving services at this store.This research method is used to describe the situation and its circumstances by using observation and interviews. With this research, the data collection method. The results showed that: 1) the way of service 2) the way of the leader 3) the consumer 4) motivation 5) discipline.